Rebranding of the resort case study: PNB Ilham Resort, Port Dickson / Siti Maisarah Abdullatif - Abdullatif, Siti Maisarah (2010)
Hospitality sector is one of the sectors that contribute to the Malaysian income. It is because, this sector have related with the Malaysia tourism sector. The continuously tourism promotion make the tourism sector more rapid and this situation have giving impact to the hospitality sector. The growths of the tourism sector make all the hotels or resort who involve in this sector has to compete each others in order to attract tourist. The competitions that exist make the hotel or resort management do some rebranding and upgrading to their hotels or resort in order to attract tourist. The objective this study is to determine the elements or things that the resort should rebranding or upgrading in order to make sure that the resort can compete with others resort in hospitality sector. The determinations of the elements and factors have been made by using comparison and analysis. Base on these two methods, the factors have been found, beside that the solution or the recommendation for the problem also have been found. Base on this study, the conclusion that can be made is this resort should carry out the rebranding process in order to compete with other resort at Port Dickson. The rebranding process should be made at the moderate scale because not all elements that have been implementing is not good and need to rebrand.